Energy cost and game dynamics in soccer: comparing sided games and repeated sprint training - Ersin Akılveren; Asuman Şahan; Emel Çetin Özdoğan (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background This study aims to propose an alternative solution for determining the optimal training load to meet the high physiological demands of football, encompassing both metabolic and locomotor loads. To this end, two different formats, repetitive sprint training (RST) and sided games (SGs), were evaluated in terms of energy cost (EC), and their similarities were revealed. Methods The study was conducted with 21 men soccer players (age: 18.24 ± 0.63 yrs, training age: 7.24 ± 0.63 yrs, body weight: 73.01 ± 7.47 kg). RST and various-sided games (4 × 4 small-sided games and 6 × 6 medium-sided games) were played according to the rules, with goalkeeper and ball possession rules tailored to different field dimensions. Both training methods were performed separately on matchday + 4 / -3 within a weekly cycle. While all SGs work for 420 s and rest for 4 min, RST performed 720 m. with 20 s rest between bouts and 4 min between sets. EC was measured using global positioning system technology during all training sessions, considering total and equivalent running distance. Results The study demonstrated that the 4v4 + Goalkeeper SSG and RST energy cost results EC cost results in similar conditioning improvement (5917.76 J/kg and 6181.00 J/kg, respectively). Conclusion As a result of the study, 4v4 + Gk SSG showed similar results regarding energy cost with RST. Additionally, it was determined that metabolic demands increased as the number of players decreased in SGs with constant m² per player.